Evaluation of the chemical composition and nutritional value of lettuce (Lactuca sativa L.) biofortified in hydroponics with iodine in the form of iodoquinolines - Dyląg, Agnieszka; Smoleń, Sylwester; Wisła-Świder, Anna; Kowalska, Iwona; Sularz, Olga; Krzemińska, Joanna; Pitala, Joanna; Koronowicz, Aneta (Frontiers in Plant Science, 2023)
Iodine deficiency in the diet creates the need to search for innovative, more sustainable and more effective strategies for enriching food with this microelement. The adopted research hypothesis assumed that the use of organic forms of iodine for supplementation of lettuce (Lactuca sativa L.), compared to mineral iodine, has a more favorable effect not only on the concentration of iodine, but also on the yield and the content of other chemical components determining its nutritional and healthpromoting value. Lettuce was planted in a nutrient film technique (NFT) hydroponic study in a greenhouse. The following application of iodine compounds (all in 5 µM molar mass equivalents) were tested in the studies: control (without of iodine application); potassium iodate (positive iodine control), 8-hydroxy-7-iodo-5-quinolinesulfonic acid, 5-chloro-7-iodo-8-quinolinol, 5,7-diiodo-8quinolinol and 4-hydroxy-8-iodo-3-quinolinecarboxylic acid. In this work, it was shown for the first time that iodoquinolines can be 1) a source of iodine for plants; 2) they have a biostimulating effect on their yielding and 3) they increase the resistance of crops to stress (due to a significant increase in the level of polyphenolic compounds). Lettuce with the addition of 8-hydroxy-7-iodo-5quinolinesulfonic acid was characterized by the highest content of iodine, which was 221.7 times higher than in control plants. The weight gain of the whole plant was particularly visible in the case of lettuce enriched with 5-chloro-7-iodo-8-quinolinol and amounted to 26.48% compared to the control. Lettuce biofortified with iodine in the form of iodoquinolines can successfully become part of a sustainable diet based on plant products, which has a low impact on the environment and contributes to the long-term good health of an individual or community. Reducing iodine deficiency through the use of organoiodine compounds can help achieve the sustainability goal of eliminating hidden hunger, improving nutritional status and promoting sustainable agriculture.